The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5296/ast.v9i1.17330
|View full text |Cite
|
Sign up to set email alerts
|

Escapement of Broodstock Chinook Salmon From Whitlock Bay Spawning Station, Lake Oahe, South Dakota

Abstract: Feral spawning fall Chinook salmon (Oncorhynchus tshawytscha) in Lake Oahe, South Dakota, are captured using a fish ladder and catch raceway at Whitlock Bay Spawning Station. The number of salmon that escaped the catch raceway and descended the fish ladder prior to spawning was unknown. During October 2017, all salmon that ascended the fish ladder at the spawning station were tagged. Tagged males remained in the catch raceway. Tagged females were moved to other secure raceways and used to estimate tag retentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Escapement of salmon broodstock from the station was erroneously assumed to be negligible for the first 33 years of operation. However, in 2017, a mark-recapture study revealed that nearly 40% of the salmon that ascended the fish ladder subsequently descended the ladder through the open weir and escaped from the station prior to spawning [13]. Re-engineering of the weir at the top of the fish ladder was recommended to increase the number of salmon retained at the station for spawning [13].…”
Section: Introductionmentioning
confidence: 99%
“…Escapement of salmon broodstock from the station was erroneously assumed to be negligible for the first 33 years of operation. However, in 2017, a mark-recapture study revealed that nearly 40% of the salmon that ascended the fish ladder subsequently descended the ladder through the open weir and escaped from the station prior to spawning [13]. Re-engineering of the weir at the top of the fish ladder was recommended to increase the number of salmon retained at the station for spawning [13].…”
Section: Introductionmentioning
confidence: 99%